Investigation of inhomogeneous degradation in large-format lithium-ion batteries. (October 2021) - Li, Xianqiang; Zeng, Tao; Qin, Honglian; Huo, Ran; Liu, Yingbo; Wei, Dexun; Ding, Xuan
Highlights: The cycling performance of large-format prismatic lithium-ion battery is greatly influenced by preloading force and mechanical properties of jelly rolls. Inhomogeneous mechanical properties of jelly rolls during cycling test lead to non-linear decreasing of capacity. Lithium plating induced by inhomogeneous pressure occurs earlier before non-linear decreasing of lithium-ion battery's capacity. The capacity decreasing of lithium-ion battery is thoroughly explained and divided into three stages. Abstract: Large-format prismatic lithium-ion batteries (LIBs) with 52 Ah capacity and Verband Der Automobilindustrie (VDA) standard dimensions were cycled under a preloading force of 2.5 kN at 25 °C. When cycled, the LIBs exhibited a two-stage degradation behavior characterized by a first linear degradation stage and a second nonlinear degradation stage. The two-stage behavior which is also called rollover failure is investigated by post-mortem analysis. When the jelly roll was unfolded, lithium plating and delamination of cathode materials were found in the curved areas. From the scanning electron microscopy (SEM) images, the graphite particles in the curved areas were deformed and cracked. The LIB under a higher preloading force of 5.5 kN was found to have shorter cycle life, indicating mechanical force is one of the factors that lead to the rollover failure. The degradation mechanism was thoroughly illustrated by applying shift voltage-resistance voltage (SV-RV), differential voltage (DV) and electrochemical impedance spectroscopy (EIS) measurements. The SV-RV analysis suggests that lithium plating occurs after around 300 cycles. The shifting to low capacity and broadening of peaks in dV/dQ curves indicate that the second nonlinear degradation stage could be caused by combining loss of active materials (LAM) and loss of lithium inventory (LLI). In the nonlinear degradation stage, ohmic resistance (Rs ) and charge transfer resistance (Rct ) is dramatically increased as characterized by EIS measurement. The increased Rs and Rct further support the conclusion that LLI and LAM are the dominating degradation mechanism in the nonlinear degradation stage.